Pengaruh Karakteristik Pemerintah Daerah Dan Temuan Audit BPK RI Terhadap Kinerja Pemerintah Daerah - Moniq Adinafa; Helmy Adam (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
This research aims to examine the influence of the characteristic of local government (size, level of wealth, dependence level, and government expenditure) and audit finding to performance of local government. Local government performance is measured by scores on the evaluation of local government performance (EKPPD). Population of this research is all the Local Government Provinces/district/cities which performance of local government had been evaluated by Ministry of Home affair in 2012. Total sample are 491 local government using purposive sampling. Result of this research indicate that size and level of wealth have significant positive influence on the performance of local government, level of dependence and government expenditure have no significant influence on the performance of local government. While audit findings have significant negative influence to the performance of local government in Indonesia. The results of this research could be used as a reference literature on performance of local government. Keywords: characteristic of local government, audit finding of The Audit Board of Republic Indonesia, the performance of local government, local government organizers report (LPPD), evaluation of local government performance (EKPPD).